Synthesis of Novel Quinacridone Dyes and Their Photovoltaic Performances in Organic Dye-sensitized Solar Cells - Sakong, Chun; Kim, Se Hun; Yuk, Sim Bum; Kim, Jeong Yun; Park, Se Woong; Ko, Min Jae; Kim, Jae Pil (WILEY-V C H VERLAG GMBH, 2011)
Two novel quinacridone (QNC) dyes with thiophene or benzene-conjugated bridge and cyanoacrylic acid acceptor were first designed and synthesized for use in dye-sensitized solar cells (DSSCs). The absorption spectra, electrochemical and photovoltaic properties of these dyes were investigated. Under simulated AM 1.5G irradiation conditions, the solar cell based on the quinacridone dye containing thiophene as a bridge unit had a short-circuit photocurrent density of 8.51 mA.cm(-2), an open-circuit voltage of 643.6 mV, and a fill factor of 0.70, corresponding to an overall conversion efficiency of 3.86%.
Keywords: CHARGE-TRANSFER; ELECTROLUMINESCENT DEVICES; MOLECULAR DESIGN; HIGHLY EFFICIENT; STATE